Key Trends and Application of Sustainability Rating Systems in the Hungarian Office Building Segment - Deutsch, Nikolett (European Scientific Journal, ESJ, 2018)
Enhancing the sustainability of buildings and construction activities has become a key issue over the last decades. Since in the European Union, the construction industry is responsible for about the 40% of the total final energy consumption, around 36% of total CO2-emission, and 32% of total waste generation it is not surprising, that the ambitious energy and climate protection goals of the EU pose enormous challenges to the sector. Although in the relevant literature there is a lack of common understanding of what sustainable and green buildings are, several quantitative and qualitative methods regarding the assessment of buildings’ sustainability, and approaches suitable for the examination of economic, social and environmental effects of buildings and the built environment have been emerged. The goal of this paper is to highlight the main principles and characters of green and sustainable buildings found in the literature, to summarize the key characteristics of the most important voluntary certification schemes applied in the European Union, and to present the current trends in the Hungarian Office market segment regarding the use of green certifications.